2022
DOI: 10.1007/s40263-022-00975-5
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Molecular and Immune-Based Therapies in Leptomeningeal Metastases

Abstract: Leptomeningeal metastases represent an aggressive stage of cancer with few durable treatment options. Improved understanding of cancer biology, neoplastic reliance on oncogenic driver mutations, and complex immune system interactions have resulted in an explosion in cancer-directed therapy in the last two decades to include small molecule inhibitors and immune checkpoint inhibitors. Most of these therapeutics are underexplored in patients with leptomeningeal metastases, limiting extrapolation of extracranial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 244 publications
(277 reference statements)
0
5
0
Order By: Relevance
“…The choice of effective systemic therapy in patients with LM is limited, mainly due to poor blood-brain barrier (BBB) penetration of systemic chemotherapy and active expulsion through efflux pumps ( 20 ). Agent selection typically varies based on tumor type and biomarker expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of effective systemic therapy in patients with LM is limited, mainly due to poor blood-brain barrier (BBB) penetration of systemic chemotherapy and active expulsion through efflux pumps ( 20 ). Agent selection typically varies based on tumor type and biomarker expression.…”
Section: Discussionmentioning
confidence: 99%
“…In 2023, Wilcox and Boire published a review exploring the pharmacology and potential for CNS penetration of several targeted agents and checkpoint inhibitors ( 20 ). Their review identified several retrospective studies and prospective trials with promising evidence for effective leptomeningeal management with systemic agents including tyrosine kinase inhibitors and immunotherapies such as nivolumab and pembrolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Several other therapeutically active strategies are under investigation in patients with brain and leptomeningeal metastases 27 , such as: Kirsten rat sarcoma viral oncogene homologue (KRAS) inhibitor adagrasib (NCT03785249); Lazertinib (third-generation EGFR-TKIs) in combination with amivantamab, an EGFR-MET bispecific antibody with immune cell-directing activity (NCT04965090); Tucatinib, a thirdgeneration reversible and highly selective HER2 inhibitor (NCT03501979); HER2 antibody-drug conjugates, trastuzumab deruxtecan (T-DXd) (NCT04420598) and HER2 chimeric antigen receptor (CAR) T cells (NCT03696030). In our cohort only few patients has been treated with any target therapy and once this therapy were not delivered intrathecal, this analysis was not formally tested, however this group of patients might have better outcomes.…”
Section: Graphic 4 Treatments Pattern Distribution Among Cohort 1 Gra...mentioning
confidence: 99%
“…Early diagnosis of leptomeningeal metastases requires a high level of suspicion. Expedited workup for a patient demonstrating subtle signs of leptomeningeal metastases, including neuraxial gadolinium-enhanced MRI and lumbar puncture, might allow for earlier initiation of CNS-targeted or CSF-penetrant systemic therapies [ 47 ]. Leptomeningeal enhancement may be absent in patients exposed to anti-angiogenic agents such as bevacizumab; careful review for subtle radiologic signs indicative of occult leptomeningeal disease including lack of sulcal T2/FLAIR suppression and/or small changes in ventricular caliber is wise.…”
Section: Headache Sub-classifications In Leptomeningeal Metastasesmentioning
confidence: 99%